2022
DOI: 10.1136/bmjopen-2021-054478
|View full text |Cite
|
Sign up to set email alerts
|

Effects of evidence-based ICU care on long-term outcomes of patients with sepsis or septic shock (ILOSS): protocol for a multicentre prospective observational cohort study in Japan

Abstract: IntroductionSepsis is not only the leading cause of death in the intensive care unit (ICU) but also a major risk factor for physical and cognitive impairment and mental disorders, known as postintensive care syndrome (PICS), reduced health-related quality of life (HRQoL) and even mental health disorders in patient families (PICS-family; PICS-F). The ABCDEF bundle is strongly recommended to overcome them, while the association between implementing the bundle and the long-term outcomes is also unknown.Methods an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 45 publications
1
2
0
Order By: Relevance
“…This study’s findings suggested that the QOL of patients with sepsis was lower than other critically ill patients, which was consistent with previous studies (8–14) indicating the need for attention to the QOL of patients with sepsis. Sepsis is an important risk factor for PICS, along with persistent systemic inflammation and multiple organ failure (28), because excessive inflammation after bioinvasive procedures spreads systemically, and the patient is susceptible to infections due to immunosuppression even in the subacute phase (14, 28).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This study’s findings suggested that the QOL of patients with sepsis was lower than other critically ill patients, which was consistent with previous studies (8–14) indicating the need for attention to the QOL of patients with sepsis. Sepsis is an important risk factor for PICS, along with persistent systemic inflammation and multiple organ failure (28), because excessive inflammation after bioinvasive procedures spreads systemically, and the patient is susceptible to infections due to immunosuppression even in the subacute phase (14, 28).…”
Section: Discussionsupporting
confidence: 92%
“…PICS is the collective term for physical, cognitive, and mental dysfunction with diverse manifestations (6, 7). Symptoms associated with PICS persist for a long time after discharge from the hospital (8–10). The quality of life (QOL) of sepsis survivors who are at high risk of PICS is low (8–14) and improves only slightly over time (15).…”
mentioning
confidence: 99%
See 1 more Smart Citation